MODEL OF EVALUATION OF THE LEVEL OF COSTS OF UNDERGROUND STORAGE OF GAS - Yaroshenko , O.L. (The actual problems of regional economy development, 2017)
In the article the research was carried out and the calculation of partial integral indicators of the level of costs of underground storage of gas was considered, allowing to consider the totality of its expenses on a separate block as one indicator and calculated the general integral indicator of the level of expenses of the enterprise in annual cut. An econometric model based on which it is possible to predict the general level of costs of an underground storage of gas, as well as to determine the degree of influence of individual factors, taking into account the influence of other factors on the general level of expenses, is constructed.